Heart failure and severe pulmonary hypertension caused by distal detachment of the valve conduit 16 years after the Cabrol composite graft procedure. - Tosoratti, E; Dall'Armellina, E; Badano, L; Frassani, R; Mazzaro, E; Zakja, E; Livi, U; Fioretti, P (2006)
We report the case of a patient who underwent Cabrol composite graft procedure for ascending aorta aneurysm and aortic regurgitation. Sixteen years later he developed progressive dyspnea and a left-to-right shunt caused by distal detachment of the valve conduit with persistence of the perigraft space-right atrial fistula visualized with echocardiography. Our case shows that late manifestations of surgical complications of the Cabrol procedure may occur and transesophageal echocardiography may allow a comprehensive assessment in these patients. However, because surgical management of ascending aorta aneurysms has changed in the last decades a detailed knowledge of the surgical technique used is mandatory for adequate interpretation of transesophageal echocardiographic results.